The Effect of Service Marketing Mix on Students Decisions to Choose State-based Vocational School - Khoirinindyah, Safitri; Sriyono, Sriyono (Master of Management Diponegoro University, 2022)
The purpose of this study was to find out the condition of the marketing mix in vocational senior high schools and to determine the simultaneous dan partial influence of product, price, location, promotion, people, facilities, and processes on the student's decisions in choosing vocation senior high school also which of the marketing mix variable has the dominant influence. The purpose of marketing in education was to build a good school image that will attract new students, marketing mix in education elements can be controlled by organizations to communicate with students and can be used to satisfy the students. The research method is quantitative research, using 195 respondents as a sample with a simple random sampling technique. Data gathering using questioner, documenting, and observation. Data analysis using multiple linear regression analysis. Hypothesis test, F test, and t-test. Results showed the simultaneous product, price, location, promotion, people, facilities, and processes influence the decisions of students, which is a positive and significant influence. Partially, products, price, location, promotion, and physical evidence have a positive and significant influence, but people and processes have no significant influence on the decisions of students. Further research could be done by adding an independent variable so it would gain another variable that influences students of school choice, for example, school image, the influence of family, etc.